Sosialisasi Merger Bank Syariah Indonesia Kepada Mahasiswa Fakultas Ekonomi dan Bisnis Islam - Suryani Suryani; Siti Marfu’ah; Ratu Humaemah (LPMP Imperium, 2022)
The development of Islamic banking in Indonesia has resulted in the merger or merger of 3 (three) existing Islamic banks, namely Bank Syariah Mandiri (BSM), Bank Negara Indonesia Syariah (BNIS) and Bank Rakyat Indonesia Syariah (BRIS). The meaning of a merger is a process of merging two companies in which one of them remains standing and uses the name of the company while the other company disappears and all of its assets are transferred to the company that remains standing. There are several types of mergers. Among others: horizontal, vertical and conglomerate mergers. The purpose of this community enggangement program (PkM) activity is to provide socialization and discussion in to students regarding the bold merger of three Islamic banks in Indonesia. Based on the results, it shows that there is an increase in students insight that is more complete regarding the merger process of Islamic banks so that it becomes an impetus for them to join as customers of Bank Syariah Indonesia, especially in the Rangkas Bitung area, Banten Province.